uji efek analgesik ekstrak kulit batang kayu akway (Drymis Sp) pada Mencit (Mus Musculus) - Tandililing, Frans Faisal (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
Analgesics or pain relievers are substances that reduce or eliminate pain without losing consciousness. One of the medicinal plants that needs to be developed is the Akway plant (Drymis Sp). Traditionally and in research, Akway bark is often used by Papuan people to cure aches and pains in joints. The research conducted tests to determine the analgesic effectiveness of akway bark (Drymis Sp) at doses of 25mg/kgBB, 50mg/kgBB, and 100mg/kgBB in mice (Mus muschulus). This research is experimental research and uses the hot-plate induction method. The results of the research that has been carried out show that at doses of 25mg/kgBB, 50mg/kgBB, and 100mg/kgBB can provide an analgesic effect. From the results of the research that has been carried out, it can be concluded that the ethanol extract of Akway bark (Drymis Sp) has the highest analgesic effect at a dose of 100 mg/kgBB.